HPLC Method Development for Estimation of Citicoline and Methylcobalamine in Tablet - Sahoo, Suraj; Kumar Panda, Prasanna; Kumar Mishra, Sagar; Sahoo, Sabuj (Asian Journal of Chemistry, 2012)
This work describes simple, accurate and precise, RP-HPLC procedure for the estimation of citicoline and methylcobalamine in tablet dosage forms. An isocratic separation was achieved using a Inertsil ODS,C18, 250 × 4.6 mm, 5 μ column with a flow rate of 1 mL/min using UV detection at 270 nm and 550 nm for citicoline and methylcobalamine respectively. The mobile phase for the separation consisted of acetonitrile:buffer (0.5 M KH2PO4 + 2.0 mL triethylamine) 25:75 v/v ratio. The retention times of citicoline and methylcobalamine were 2.25 and 6.71 min, respectively. The method was statistically validated for linearity, accuracy and precision. The linearity of citicoline and methylcobalamine shows a correlation coefficient of 0.999 and 0.999. The method was reproducible with intra and inter-day variations. The simplicity and accuracy of the proposed method ensures its use in routine quality control analysis of pharmaceutical formulations. The method established is robust, resisting small deliberate changes in flow rate and the ratio of the organic components in the mobile phase which is useful for the routine determination of citicoline and methylcobalamine in its pharmaceutical dosage form.